2012
DOI: 10.1208/s12248-012-9372-3
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Modeling Tools to Drive Efficient Oral Product Design

Abstract: Abstract. Modeling and simulation of drug dissolution and oral absorption has been increasingly used over the last decade to understand drug behavior in vivo based on the physicochemical properties of Active Pharmaceutical Ingredients (API) and dosage forms. As in silico and in vitro tools become more sophisticated and our knowledge of physiological processes has grown, model simulations can provide a valuable confluence, tying-in in vitro data with in vivo data while offering mechanistic insights into clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…The aqueous solubility is almost eight times higher at neutral pH than at pH in the range of 1.2-6. The pK a and logD values are 4.85 and 5.09, respectively (25). The P eff value is 5,000 cm/s.…”
Section: Drug Molecule Physicochemical Propertiesmentioning
confidence: 94%
See 4 more Smart Citations
“…The aqueous solubility is almost eight times higher at neutral pH than at pH in the range of 1.2-6. The pK a and logD values are 4.85 and 5.09, respectively (25). The P eff value is 5,000 cm/s.…”
Section: Drug Molecule Physicochemical Propertiesmentioning
confidence: 94%
“…When kinetic biorelevant media solubility, i.e., FaSSIF and FeSSIF, was included in the model, the model predicted the fasted-state clinical data but not the fed-state data. Solubility experiments showed that the drug was very soluble in digestible lipids and subsequent experiments, where additional lipid was included in the FeSSIF, indicated a greater than tenfold increase in drug solubility from 109 μg/ml in FaSSIF media to 1,340 μg/ml in FeSSIF+Microlipid media (all adjusted to pH 6.3) (25). The model was run using FeSSIF+ Microlipid media, assuming a 1 h gastric emptying T 50 (as is typically observed with a highfat meal).…”
Section: In Silico Modeling Using Gastroplus® Softwarementioning
confidence: 95%
See 3 more Smart Citations